Mediating belonging: English-language media and international student integration in urban China — A case study of Shanghai’s foreign media ecosystem - Chen, Zeling (Edelweiss Applied Science and Technology, 2025)
With the increasing number of international students in Chinese cities, English-language media plays a crucial role in facilitating access to information, fostering cultural understanding, and supporting local integration. This study examines the extent to which English-language media in Shanghai meets the specific needs of international students. Employing a mixed-methods approach that combines survey data, in-depth interviews, and content analysis, the research explores media consumption behaviors, satisfaction levels, and key barriers to engagement. Findings indicate that mobile-based platforms, particularly WeChat, are central to students’ daily media use due to their accessibility, practical content, and multifunctionality. Traditional outlets such as China Daily and CGTN are widely recognized but are rarely used, primarily because of limited interactivity, language barriers, and lack of localized relevance. Students report a strong preference for service-oriented information, including guidance on food, housing, events, and student policies, rather than general news or political content. While Chinese English-language media contributes to improved perceptions of Shanghai and China, it falls short in promoting entertainment engagement and meaningful social integration. The study argues that bilingual, user-centered, and service-driven media strategies are essential for enhancing international students’ media experiences and supporting their adjustment in urban China. Recommendations are proposed to improve content design, platform selection, linguistic accessibility, and user interaction. The findings offer practical insights for media practitioners, policymakers, and researchers focused on cross-cultural communication, urban inclusivity, and international education.